PENGARUH EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR PKN KELAS IV MIN BANGKA BELITUNG - Nurhayati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractA common problem in this research is “how is the influence of example non example model on student learning outcomes in the subject of civics education grade 4 Madrasah Ibtidaiyah Negeri Bangka Belitung Southeast Pontianak.study aims to find out how much influence example non example results on student learning outcomes on the subject of citizenship education grade 4 Madrasah Ibtidaiyah Negeri Bangka Belitung Southeast Pontianak. Research method is experimental method. The form of research used in this study is quasy experiment, with research design posstest only control design. Population in this study were all 4th graders Madrasah Ibtidaiyah Negeri Bangka Belitung Southeast Pontianak.which consists of two classes namely class 4A and 4B. The data collections instrument used is a measurement techniquean data collection tools in the form of text of students learning outcomes in the form of essay with the amountof 10 questions. Based on the calculation result obtained average pretest experiment class 33,56 and average pretest control class 26,5. Posttest experiment class 70,38 and posttest control class 62,25. Then form the calculation of t test obtained price = 1,6759. Evidently (2,8626) (1,6759), then accepted and rejected form the calculation effect size 0,82 belong to the high category, this means learning by applying the model example non example give influence to the result of learning of citizenship educations grade 4 Madrasah Ibtidaiyah Negeri Bangka Belitung Southeast Pontianak. Keywords: influence, example non example, learning outcomes, civic education.